Translator Education and Sustainability - Kim, Mira (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe paper presents a classroom-based action research project that I undertook as a participant in the action research project, Action research for Change Towards Sustainability (ACTS): Change in Curricula and Graduate Skills Towards Sustainability in 2003-2004. The classroom-based action research explored the question of how to incorporate sustainability in translator education. The research adopted social constructivism as a teaching approach to achieve the goal of education for sustainability. The whole process was studied by means of action research. The research found that collaborative project-based teaching is a highly efficacious method to improve translation skills and generic skills required for sustainability.